Paradigma Holistik-Integratif-Interkonektif Dalam Filsafat Manajemen Pendidikan Karakter - Maragustam Maragustam (Jurnal Studi Agama dan Masyarakat, 2015)
This paper analyzes the thought of philosophy of education management character of the nation with a philosophical method. The results of the discussion can be concluded that it needed a new paradigm in the management philosophy of education that is holistic-integrative character-interkonektif. The essence of management lies in POAC (planning, organizing, actuating and controlling). In character education management philosophy with the new paradigm is to be done thoroughly, connectedness and relatedness between one system with other systems. As a holistic-integrative-interkonektif in the level of strategy (habituation, moral knowing, moral loving-feeling, exemplary and repentance), the level of educational institutions (formal, informal and non-formal), the level of the main values of character, level kurkukulum (intra-curricular, extra curricular and hidden curriculum), the level of age (early childhood, adolescence, adulthood, and old age) and the level of mental gymnastics (if thought, hearts, taste-intention, spiritual and physical). With this paradigm, the management philosophy of character education will form a good character-solid man who is ready to face the impact of globalization is challenging and uncertain particularly negative impact.